Gothic art - Gunderson, Jessica (Mankato, Minn. : Creative Education, 2009)
Examines the birth and decline of the Gothic movement in art, looks at the political and social events that sparked the medieval movement, and introduces representative artists and works.
Includes bibliographical references (p. 47) and index.
8.3
5-8
Keywords: Architecture, Gothic -- Juvenile literature; Art, Gothic -- Juvenile literature; Architecture, Gothic; Art, Gothic; Gothic architecture; Gothic art